Productivity of sugarcane plants of ratooning with fertilizing treatment - A. SUTOWO LATIEF; RIZAL SYARIEF; BAMBANG PRAMUDYA; MUHADIONO MUHADIONO (Nusantara Bioscience, 2010)
Abstract. Latief AS, Syarief R, Pramudya B, Muhadiono. 2010. Productivity of sugarcane plants of ratooning with various fertilizing treatments. Nusantara Bioscience 2: 43-47. This research aims to determine the sugarcane plants of ratooning productivity with low external input of fertilization treatment towards farmers can increase profits. The method used is the Completely Randomized Block Design (CRBD) with four treatments and three repetitions (4x3). Sugarcane varieties R 579 planted in each patch experiment 5x5 m2. Dosage of fertilizer: P0 = 3.6 kg/year plot experiment was 100% dosage usage of chemical fertilizers used by farmers. Further dosages were P1 (75%) = 2.7 kg/plot, P2 (50%) = 1.8 kg/plot and P3 (0.25%) = 0.9 kg/plot, each supplemented with fertilizer 5 mL of liquid organic/patch a year. Sugarcane crops with a variety of treatment showed no significant difference. The highest productivity was achieved at dosages of P2 (50% chemical fertilizers plus organic fertilizer) is 21.67 kg per square meter. Chemical fertilizers can be saved 7 quintals per hectare a year or Rp 997,500 per year. Additional costs of liquid organic fertilizer Rp. 100,000 per hectare year and labor Rp 100,000 per hectare, so the additional advantage of saving farmers fertilizer Rp. 797,500 per year.